Penerapan Model Pembelajaran Tipe JIGSAW Untuk Meningkatkan Hasil Belajar Matematika Siswa Pada Materi Polinomial Di Kelas XI-MIA 1 SMA N 1 Angkola Timur - Zalmi Nauli Harahap; Nurdalilah; Nova Christina Dewi (Program Studi Matematika Universitas Graha Nusantara Padangsidimpuan, 2025)
This study aims to determine the effectiveness of the Jigsaw cooperative learning model in improving students' mathematics learning outcomes on polynomial material in class XI MIA 1 at SMA Negeri 1 Angkola Timur. The background of this study is the low learning outcomes of students, as indicated by average scores that have not reached the Minimum Passing Criteria (KKM). This research used the Classroom Action Research (CAR) method, which was carried out in two cycles, each consisting of the planning, implementation, observation, and reflection stages. The research subjects were 23 students with instruments in the form of learning outcome tests and student activity observation sheets. The results showed an increase in both the mastery of learning outcomes and student activity. In cycle I, the percentage of student learning mastery was only 57%, then increased in cycle II to 82.61%. Student learning activities also increased from 65.70% in cycle I to 85.53% in cycle II. Thus, it can be concluded that the application of the Jigsaw learning model is effective in improving student mathematics learning outcomes.